2008
DOI: 10.1097/hjh.0b013e328302842b
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of waist circumference for the identification of childhood hypertension

Abstract: High blood pressure is strongly associated with excess weight. Waist circumference improves the ability of BMI to identify hypertension in obese children. Waist circumference is related to absolute blood pressure values in all weight classes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
68
1
11

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 37 publications
7
68
1
11
Order By: Relevance
“…Regarding AO, a previous study assessing the association between fat distribution and cardiovascular risk in children showed that visceral fat (as well as total fat) is associated to high BP in Italian children [99]. This association has also been established by several researchers [28,61,94,[100][101][102][103][104][105][106].…”
Section: Hypertensionmentioning
confidence: 79%
“…Regarding AO, a previous study assessing the association between fat distribution and cardiovascular risk in children showed that visceral fat (as well as total fat) is associated to high BP in Italian children [99]. This association has also been established by several researchers [28,61,94,[100][101][102][103][104][105][106].…”
Section: Hypertensionmentioning
confidence: 79%
“…pre-prandial and postprandial period) and it is more practical especially in winter and at busy healthcare sites. In addition, an established standard for the measurement of WC is lacking (31), and the use of WC did not improve the strength of BMI to identify high blood pressure in normal weight children and adolescents (26,32). Therefore, we suggest that NC is a better predictor in normal weight children and adolescents for elevated blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…5 Genovesi y cols. hallaron una fuerte asociación entre la hipertensión y el aumento de peso y de la circunferencia de la cintura, 28 mientras que Maffei y cols. observaron una correlación positiva entre el aumento de la medida de circunferencia de la cintura, la resistencia a la insulina y la hipertensión.…”
Section: Discussionunclassified